2016
DOI: 10.1249/mss.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise Hypotension after Heart Transplant

Abstract: HEx and LEx promoted similar reductions in ABP of heart transplant recipients, which suggests that they may be a tool to counteract hypertension in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Recent studies have suggested that HEx may be a superior alternative to traditional LEx for hypertension management, due to the large ambulatory BP reductions found after both 2 wk (average 12/9 mmHg reduction in 24-h systolic/diastolic BP) [21] and 12 wk (average 24/12 mmHg reduction in 24-h systolic/diastolic BP) [22] of training in patients with resistant hypertension, which were greater than the reductions found after 8-12 wk of LEx (average 6/3 mmHg reduction in daytime systolic/diastolic BP only) [18]. Although a previous study by our group showed that HEx and LEx promoted similar reductions in ambulatory BP in heart transplant recipients [4], a recent study showed greater resting BP reductions after HEx than LEx in both treated and untreated older hypertensives [2]. However, this previous study measured only resting BP up to 90 min after exercise cessation.…”
Section: Hexmentioning
confidence: 54%
See 3 more Smart Citations
“…Recent studies have suggested that HEx may be a superior alternative to traditional LEx for hypertension management, due to the large ambulatory BP reductions found after both 2 wk (average 12/9 mmHg reduction in 24-h systolic/diastolic BP) [21] and 12 wk (average 24/12 mmHg reduction in 24-h systolic/diastolic BP) [22] of training in patients with resistant hypertension, which were greater than the reductions found after 8-12 wk of LEx (average 6/3 mmHg reduction in daytime systolic/diastolic BP only) [18]. Although a previous study by our group showed that HEx and LEx promoted similar reductions in ambulatory BP in heart transplant recipients [4], a recent study showed greater resting BP reductions after HEx than LEx in both treated and untreated older hypertensives [2]. However, this previous study measured only resting BP up to 90 min after exercise cessation.…”
Section: Hexmentioning
confidence: 54%
“…24-h ABP monitoring started 90 min after each intervention, at the same time of the day (11:00-11:30 a.m.), and was performed on a weekday other than Friday with a Dyna-Mapa™ ABP monitor (Cardios Sistemas Comercial e Industrial Ltda, Sao Paulo, Brazil), as previously described [4]. In brief, the monitor was programmed to measure BP every 15 min during daytime and every 20 min during nighttime periods (based on participants' time from getting into and out of bed).…”
Section: Ambulatory Blood Pressure Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…24-h ABP monitoring started min after each intervention, at the same time of the day (5:00 to 6:00 p.m.), and was performed on a weekday other than Friday with a Dyna-Mapa ABP monitor (Cardio Sistemas Comercial e Industrial Ltda, Sao Paulo, Brazil), as previously described (Castro et al 2016). In brief, the monitor was programmed to measure BP every 15 min during daytime and every 20 min during nighttime periods (based on participants' time from getting into and out of bed).…”
Section: Ambulatory Blood Pressure Monitoringmentioning
confidence: 99%